Glass-based fluorescent ceramic material as well as preparation method and application thereof

By combining garnet-based fluorescent ceramics with Eu2+ and Mn2+ red fluorescent elements in Bi2O3-B2O3-SiO2-Na2O-MxO glass system, glass-based fluorescent ceramic materials with high color development index and excellent optical properties were prepared, and the existing solutions were solved White LED materials have thermal stability and light color problems, and are suitable for high-power LED lighting.

CN119118705AActive Publication Date: 2024-12-13FUJIAN INST OF RES ON THE STRUCTURE OF MATTER CHINESE ACAD OF SCI +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202310691292.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-12
Publication Date
2024-12-13
Estimated Expiration
2043-06-12

AI Technical Summary

Technical Problem

The organic packaging materials of existing white LEDs have low heat resistance and thermal conductivity, resulting in reduced luminous efficiency and discoloration. The light obtained by a single YAG:Ce yellow phosphor lacks red components, which cannot meet the lighting needs of high color rendering index.

Method used

Garnet-based fluorescent ceramics are used as the substrate, combined with red fluorescent elements such as Eu2+, Mn2+ in Bi2O3-B2O3-SiO2-Na2O-MxO glass system, and glass-based fluorescent ceramic materials are prepared by low melting temperature, and fluorescent powder is used as the red fluorescent source. , improve thermal stability and optical performance.

Benefits of technology

It achieves high color rendering index and excellent optical performance, is suitable for lighting needs of high-power LEDs, avoids the erosion of red phosphors at high temperatures, and improves the thermal conductivity and chemical stability of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119118705A_ABST
    Figure CN119118705A_ABST
Patent Text Reader

Abstract

The invention discloses a glass-based fluorescent ceramic material as well as a preparation method and application thereof. The glass-based fluorescent ceramic material comprises a substrate and a fluorescent glass film, wherein the fluorescent glass film is arranged on at least one surface of the substrate; the substrate is selected from garnet-based fluorescent ceramic; the fluorescent glass film at least comprises a glass body and a fluorescent element; and the thickness ratio of the substrate to the fluorescent glass film is (20: 1)-(50: 1). The glass-based fluorescent ceramic material disclosed by the invention has the outstanding advantages of good thermal stability, good optical performance and the like, and is used for packaging to obtain an LED light source to obtain high-luminous-efficiency and high-color-rendering-index illumination.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a glass-based fluorescent ceramic material and a preparation method and application thereof, belonging to the field of solid luminescent materials. Background Art

[0002] White light emitting diodes (WLEDs) have been widely used in solid-state lighting due to their environmental protection, high efficiency, long life, and energy saving. Currently, the preparation method of commercial white light LEDs is to combine blue light chips with YAG:Ce yellow phosphors and embed them into silica gel or organic resin. However, for high-power WLEDs, the heat resistance and thermal conductivity (0.1-0.4Wm -1 K -1 ) is low, which will lead to reduced luminous efficacy and serious discoloration after long-term use.

[0003] Compared with organic resin or silica gel, glass has higher thermal conductivity and good chemical stability, and can effectively protect phosphor particles, thereby improving luminous efficiency and extending service life. At present, fluorescent glass and fluorescent glass film with glass as the substrate are more studied. Patent CN105399325 discloses a Ce:YAG fluorescent glass for white light LED and its preparation method, characterized in that PbO, B2O3, ZnO and SiO2 are mixed evenly, then melted at high temperature (about 1000°C), and glass slag is obtained after water quenching, and then the crushed glass slag powder is mixed with YAG:Ce phosphor to sinter into fluorescent glass. The fluorescent glass uses the toxic raw material PbO, which is not conducive to safe production. In addition, the light obtained by using a single YAG:Ce yellow phosphor is cold white light. This white light often shows high color temperature and low color rendering index due to the lack of red components, and cannot be used in lighting fields requiring high color rendering index and low color temperature.

[0004] Compared with fluorescent glass or glass-based fluorescent glass films, fluorescent ceramics are considered to be the best choice for phosphor converters because they have better thermal conductivity and thermal stability. Therefore, it is of great significance to develop a high-CRI fluorescent glass film based on YAG-based fluorescent ceramics. Summary of the invention

[0005] To solve the above problems, the present invention provides the following technical solutions:

[0006] A glass-based fluorescent ceramic material comprises a substrate and a fluorescent glass film. The fluorescent glass film is arranged on at least one surface of the substrate, for example, on any one surface, or on both surfaces.

[0007] According to an embodiment of the present invention, the substrate is selected from garnet-based fluorescent ceramics. Preferably, the garnet-based fluorescent ceramics are selected from YAG-based fluorescent ceramics and LuAG-based fluorescent ceramics, such as YAG:Ce, LuAG:Ce, and YLuAG:Ce.

[0008] According to an embodiment of the present invention, the thickness ratio of the substrate to the fluorescent glass film is 20:1-50:1, for example, 50:1.

[0009] According to an embodiment of the present invention, the fluorescent glass film at least includes a glass body and a fluorescent element.

[0010] According to an embodiment of the present invention, the fluorescent element is uniformly distributed in the glass body.

[0011] According to an embodiment of the present invention, the content of the fluorescent element in the fluorescent glass film is 0.003-0.009 wt %, for example, 0.006 wt %.

[0012] According to an embodiment of the present invention, the glass body is selected from Bi2O3-B2O3-SiO2-Na2O-M x O glass system, in which the oxide M x In O, M is selected from at least one of Li, Zn, Al, P, Ba, and Ga, and x is selected from 1-3, for example, 1, 2, or 3.

[0013] According to an embodiment of the present invention, the fluorescent element is selected from elements having red fluorescence, such as Eu 2+ , Mn 2 + , Mn 4+ At least one of .

[0014] Preferably, the element with red fluorescence is provided by phosphor. Further, the phosphor is selected from (Sr, Ca)AlSiN3:Eu 2+ Phosphor, CaAlSiN3:Eu 2+ Phosphor, Sr2Si5N8:Eu 2+ At least one of the phosphors.

[0015] According to an embodiment of the present invention, the fluorescent glass film is prepared by the following method: glass powder is mixed with the fluorescent powder and sintered.

[0016] Preferably, the phosphor accounts for 0.1 wt%-80 wt% of the total mass of the powder of the glass body and the phosphor, for example, 50 wt%.

[0017] Preferably, the particle size of the glass powder is not greater than 80 microns, for example, 23 microns.

[0018] The present invention also provides a method for preparing the above-mentioned glass-based fluorescent ceramic material, the preparation method comprising the following steps:

[0019] (1) Preparation of glass powder: After melting the glass body, it is rapidly cooled to obtain glass powder;

[0020] (2) mixing the phosphor with the glass powder obtained in step (1), and adding an organic solvent to prepare a slurry;

[0021] (3) coating the slurry of step (2) on the surface of the substrate, drying and sintering to obtain the glass-based composite fluorescent ceramic.

[0022] According to an embodiment of the present invention, in step (1), the glass body has the meaning as described above. Preferably, the glass body can be prepared by a method known in the art, for example, by mixing raw materials with a stoichiometric ratio and melting them at high temperature. In the present invention, the high-temperature melting can be a temperature known in the art, for example, above 800°C, and for example, 950°C or 1000°C. Preferably, after the high-temperature melting, it can also be kept warm, and the keeping warm time is, for example, 0min-60min, and for example, 30min.

[0023] According to an embodiment of the present invention, in step (1), the melting temperature is above 800°C, preferably 850-950°C, for example 950°C, 1000°C.

[0024] According to an embodiment of the present invention, in step (1), the melting time is 30 min-120 min, for example, 60 min.

[0025] According to an embodiment of the present invention, in step (1), after melting, a heat preservation treatment may be further performed, wherein the heat preservation treatment refers to heat preservation at the melting temperature, and the heat preservation time is 10 min-60 min, for example, 30 min.

[0026] According to an embodiment of the present invention, in step (1), the quenching treatment comprises quenching the molten glass at 0-100° C., and optionally crushing and grinding. Preferably, after grinding, the glass powder is passed through a 200-300 mesh sieve.

[0027] According to an embodiment of the present invention, in step (2), the organic solvent is selected from alcohols and cellulose. Preferably, the alcohol is selected from at least one of terpineol and isopropyl alcohol. Preferably, the cellulose is selected from ethyl cellulose.

[0028] According to an embodiment of the present invention, in step (2), the mass ratio of oleyl alcohol to cellulose is 1-30:1, for example, 20:1.

[0029] Exemplarily, the organic solvent consists of terpineol and ethyl cellulose, and the mass ratio of terpineol to ethyl cellulose is 20:1.

[0030] According to an embodiment of the present invention, the amount of the organic solvent used in the present invention is not specifically limited, as long as the slurry can be obtained. Exemplarily, the mass ratio of the glass powder to the organic solvent is 1:3.

[0031] According to an embodiment of the present invention, in step (2), the phosphor accounts for 0.1 wt%-80 wt%, for example, 50 wt%, of the total mass of the glass powder and the phosphor.

[0032] According to an embodiment of the present invention, in step (3), during coating, the amount of the slurry and the substrate is not specifically limited, as long as the glass-based composite fluorescent ceramic can be obtained. Exemplarily, the mass ratio of the slurry to the substrate is 2:3.

[0033] According to an embodiment of the present invention, in step (3), the drying is performed at a temperature below 100°C, for example, 70°C.

[0034] According to an embodiment of the present invention, in step (3), the sintering conditions include: a sintering temperature of 400°C-600°C and a holding time of 10-30 minutes. Exemplarily, the sintering temperature is 530°C and the holding time is 30 minutes.

[0035] The present invention also provides application of the glass-based fluorescent ceramic material in high-power LEDs.

[0036] According to the embodiment of the present invention, the high-power LED refers to an LED with a rated current exceeding 20 mA, such as a 670 mA constant current drive.

[0037] Beneficial effects of the present invention:

[0038] (1) The present invention develops a glass with a low melting temperature, solves the problem of high temperature glass corroding nitride red phosphor, and successfully prepares a glass-based fluorescent ceramic material. The prepared glass-based fluorescent ceramic material has outstanding advantages such as good thermal stability and good optical properties.

[0039] (2) The glass-based fluorescent ceramic material of the present invention uses YAG-based fluorescent ceramic as a substrate, and has a good heat dissipation effect. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 This is the transmittance curve of the glass: it shows that the prepared glass has a higher transmittance.

[0041] Figure 2The emission spectrum of the glass-based fluorescent ceramic material in Example 1-4: There is an obvious emission peak at 603nm, which is (Sr,Ca)AlSiN3:Eu 2+ The main emission peak of (Sr,Ca)AlSiN3:Eu 2+ With the increase of phosphor concentration, the emission peak of red phosphor becomes stronger and red-shifted, which is consistent with the actual situation. DETAILED DESCRIPTION

[0042] The technical scheme of the present invention will be further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only exemplary descriptions and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.

[0043] Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.

[0044] Example 1

[0045] The preparation method of glass-based fluorescent ceramic material is as follows:

[0046] (1) Preparation of glass powder: 58 wt% Bi2O3, 20 wt% B2O3, 10 wt% SiO2, 4 wt% ZnO, 3 wt% Al2O3, 4 wt% Na2O, and 1 wt% Li2O are taken into an agate mortar, and the above raw materials are mixed evenly and put into a platinum crucible. After the muffle furnace is heated to 950°C, the platinum crucible is placed therein and kept warm for 60 min. After the insulation is completed, the platinum crucible is taken out, and the glass melt in the platinum crucible is rapidly cooled in the air to obtain glass blocks. The glass blocks are broken and ground into a mortar, and then passed through a 300-mesh sieve to obtain glass powder.

[0047] (2) (Sr,Ca)AlSiN3:Eu 2+ The red phosphor and the glass powder of step (1) are weighed in a ratio of 1:1 (mass ratio), and after the two are evenly mixed, an organic solvent (composed of pine alcohol and ethyl cellulose, the mass ratio of pine alcohol and ethyl cellulose is 20:1, and the mass ratio of the organic solvent to the glass powder is 3:1) is added to prepare a slurry, and then the slurry is coated on one surface of a YAG:Ce ceramic substrate by spin coating to obtain a glass film, wherein the thickness ratio of the glass film to the ceramic substrate is 1:50, and the coated ceramic sheet is placed in an oven at 70°C for 8 hours. Finally, the dried ceramic sheet is placed in a muffle furnace for sintering at 530°C, and taken out after keeping warm for 30 minutes to obtain a glass-based fluorescent ceramic material.

[0048] The glass-based fluorescent ceramic material of this embodiment and the blue light chip are packaged into an LED device. At room temperature, a 670mA constant current drive is applied, and the measured performance parameters are as follows:

[0049] Luminous efficiency: 98.35lm / W; Color rendering index: 72.2.

[0050] Example 2

[0051] The preparation method of glass-based fluorescent ceramic material is as follows:

[0052] (1) Preparation of glass powder: 58 wt% Bi2O3, 20 wt% B2O3, 10 wt% SiO2, 4 wt% ZnO, 3 wt% Al2O3, 4 wt% Na2O, and 1 wt% Li2O are taken into an agate mortar, and the above raw materials are mixed evenly and put into a platinum crucible. After the muffle furnace is heated to 950°C, the platinum crucible is placed therein and kept warm for 60 min. After the insulation is completed, the platinum crucible is taken out, and the glass melt in the platinum crucible is rapidly cooled in the air to obtain glass blocks. The glass blocks are broken and ground into a mortar, and then passed through a 300-mesh sieve to obtain glass powder.

[0053] (2) (Sr,Ca)AlSiN3:Eu 2+ The red phosphor and the glass powder of step (1) are weighed in a ratio of 1:1.5 (mass ratio), and after the two are evenly mixed, an organic solvent (composed of pine alcohol and ethyl cellulose, the mass ratio of pine alcohol and ethyl cellulose is 20:1, and the mass ratio of the organic solvent to the glass powder is 3:1) is added to prepare a slurry, and then the slurry is coated on one surface of a YAG:Ce ceramic substrate by spin coating to obtain a glass film, wherein the thickness ratio of the glass film to the ceramic substrate is 1:50, and the coated ceramic sheet is placed in an oven at 70°C for 8 hours. Finally, the dried ceramic sheet is placed in a muffle furnace for sintering at 530°C, and taken out after keeping warm for 30 minutes to obtain a glass-based fluorescent ceramic material.

[0054] The glass-based fluorescent ceramic material of this embodiment and the blue light chip are packaged into an LED device. At room temperature, a 670mA constant current drive is applied, and the measured performance parameters are as follows:

[0055] Luminous efficiency: 115.99lm / W; Color rendering index: 74.5.

[0056] It can be seen that the glass-based fluorescent ceramic material in this embodiment has excellent light color performance and can meet the demand for high-power LED lighting.

[0057] Example 3

[0058] The preparation method of glass-based fluorescent ceramic material is as follows:

[0059] (1) Preparation of glass powder: 58 wt% Bi2O3, 20 wt% B2O3, 10 wt% SiO2, 4 wt% ZnO, 3 wt% Al2O3, 4 wt% Na2O, and 1 wt% Li2O are taken into an agate mortar, and the above raw materials are mixed evenly and put into a platinum crucible. After the muffle furnace is heated to 950°C, the platinum crucible is placed therein and kept warm for 60 min. After the insulation is completed, the platinum crucible is taken out. At this time, the glass melt in the platinum crucible is rapidly cooled in the air into glass blocks. The glass blocks are broken and put into a mortar for grinding, and passed through a 300-mesh sieve to obtain glass powder.

[0060] (2) (Sr,Ca)AlSiN3:Eu 2+ The red phosphor and the glass powder of step (1) were weighed in a ratio of 1:2, and the YAG:Ce fluorescent ceramic sheet was ground to 0.4 mm. Other conditions were the same as those in Example 1 to obtain a glass-based fluorescent ceramic material.

[0061] The glass-based fluorescent ceramic material of this embodiment and the blue light chip are packaged into an LED device. At room temperature, a 670mA constant current drive is applied, and the measured performance parameters are as follows:

[0062] Luminous efficiency: 77.44lm / W; Color rendering index: 81.6.

[0063] It can be seen that the glass-based fluorescent ceramic material in this embodiment has excellent light color performance and can meet the demand for high-power LED lighting.

[0064] Example 4

[0065] The preparation method of glass-based fluorescent ceramic material is as follows:

[0066] (1) Preparation of glass powder: 58 wt% Bi2O3, 20 wt% B2O3, 10 wt% SiO2, 4 wt% ZnO, 3 wt% Al2O3, 4 wt% Na2O, and 1 wt% Li2O are taken into an agate mortar, and the above raw materials are mixed evenly and put into a platinum crucible. After the muffle furnace is heated to 950°C, the platinum crucible is placed therein and kept warm for 60 min. After the insulation is completed, the platinum crucible is taken out. At this time, the glass melt in the platinum crucible is rapidly cooled in the air into glass blocks. The glass blocks are broken and put into a mortar for grinding, and passed through a 300-mesh sieve to obtain glass powder.

[0067] (2) (Sr,Ca)AlSiN3:Eu 2+ The red phosphor and the glass powder of step (1) are weighed in a ratio of 1:3, and other conditions are the same as those in Example 1 to obtain a glass-based fluorescent ceramic material.

[0068] The glass-based fluorescent ceramic material of this embodiment and the blue light chip are packaged into an LED device. At room temperature, a 670mA constant current drive is applied, and the measured performance parameters are as follows:

[0069] Luminous efficiency: 107.31lm / W; Color rendering index: 71.2.

[0070] It can be seen that the glass-based fluorescent ceramic material in this embodiment has excellent light color performance and can meet the demand for high-power LED lighting.

[0071] Comparative Example 1

[0072] The preparation method of fluorescent glass is as follows:

[0073] (1) Preparation of glass powder: Powder raw materials are weighed according to 52 mol% PbO, 33 mol% B2O3, 10 mol% ZnO, and 5 mol% SiO2, mixed and melted at 800°C for 3 hours to prepare glass powder.

[0074] (2) Take the glass powder from step (1) and add 5wt% YAG:Ce phosphor and 5wt% (Sr,Ca)AlSiN3:Eu 2+ The red phosphor is mixed and placed in a crucible, which is then directly placed in a resistance furnace at 600°C. After being kept warm for 30 minutes, it is formed and annealed at 300°C to obtain fluorescent glass.

[0075] The prepared fluorescent glass is opaque and has a low hardness, and its luminescence performance cannot be measured.

[0076] It can be seen that the fluorescent glass prepared by adding yellow and red phosphors in this comparative example is opaque and has a low hardness. Compared with Example 1, it can be seen that the glass-based fluorescent ceramics in the present invention have superior performance.

[0077] Comparative Example 2

[0078] The preparation method of glass-based fluorescent ceramic material is as follows:

[0079] (1) Preparation of glass powder: 58 wt% Bi2O3, 20 wt% B2O3, 10 wt% SiO2, 4 wt% ZnO, 3 wt% Al2O3, 4 wt% Na2O, and 1 wt% Li2O are put into an agate mortar, and the raw materials are mixed evenly and put into a platinum crucible. After the muffle furnace is heated to 950°C, the crucible is kept warm for 60 min. After the muffle furnace is heated, the crucible is taken out and rapidly cooled in the air, broken into pieces, ground into a mortar, and passed through a 300-mesh sieve to obtain glass powder.

[0080] (2) (Sr,Ca)AlSiN3:Eu 2+The red phosphor and the glass powder of step (1) are weighed in a ratio of 9:1, and other conditions are the same as those in Example 1 to obtain a glass-based fluorescent ceramic material.

[0081] Since less glass powder is added to the glass-based fluorescent ceramic material, it is difficult for the fluorescent powder to stick to the ceramic sheet and the fluorescent powder can be easily scraped off the ceramic sheet.

[0082] Comparative Example 3

[0083] The preparation method of glass-based fluorescent ceramic material is as follows:

[0084] (1) Preparation of glass powder: 58 wt% Bi2O3, 20 wt% B2O3, 10 wt% SiO2, 4 wt% ZnO, 3 wt% Al2O3, 4 wt% Na2O, and 1 wt% Li2O are put into an agate mortar, and the raw materials are mixed evenly and put into a platinum crucible. After the muffle furnace is heated to 950°C, the crucible is kept warm for 60 min. After the muffle furnace is heated, the crucible is taken out and rapidly cooled in the air, broken into pieces, ground into a mortar, and passed through a 300-mesh sieve to obtain glass powder.

[0085] (2)K2SiF6:Mn 4+ The red phosphor and the glass powder of step (1) are weighed in a ratio of 1:1, and other conditions are the same as those in Example 1 to obtain a glass-based fluorescent ceramic material.

[0086] Since K2SiF6:Mn 4+ The thermal stability of red phosphor is poor, which causes the phosphor to turn black after being co-sintered with glass powder at 530°C, and its luminescence performance cannot be measured. 4+ Red phosphor is not suitable for this method.

[0087] The above is a description of the exemplary embodiments of the present invention. However, the protection scope of the present application is not limited to the above embodiments. Any modification, equivalent substitution, improvement, etc. made by those skilled in the art within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A glass-based fluorescent ceramic material, characterized in that: It includes a substrate and a fluorescent glass film, wherein the fluorescent glass film is arranged on at least one surface of the substrate; The substrate is selected from garnet-based fluorescent ceramics; The fluorescent glass film at least includes a glass body and fluorescent elements.

2. The glass-based fluorescent ceramic material according to claim 1, characterized in that: The garnet-based fluorescent ceramic is selected from YAG-based fluorescent ceramics and LuAG-based fluorescent ceramics. Preferably, the fluorescent elements are uniformly distributed in the glass body. Preferably, the content of the fluorescent element in the fluorescent glass film is 0.003-0.009 wt %. Preferably, the thickness ratio of the substrate to the fluorescent glass film is 20:1-50:

1.

3. The glass-based fluorescent ceramic material according to claim 1 or 2, characterized in that: The glass body is selected from Bi2O3-B2O3-SiO2-Na2O-M x O glass system, in which the oxide M x In O, M is selected from at least one of Li, Zn, Al, P, Ba and Ga, and x is selected from 1-3. Preferably, the fluorescent element is selected from elements having red fluorescence.

4. The glass-based fluorescent ceramic material according to any one of claims 1 to 3, characterized in that: The fluorescent glass film is prepared by the following method: mixing the powder of the glass body with the fluorescent powder and sintering them.

5. The method for preparing the glass-based fluorescent ceramic material according to any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: (1) Preparation of glass powder: After melting the glass body, it is rapidly cooled to obtain glass powder; (2) mixing the phosphor with the glass powder obtained in step (1), and adding an organic solvent to prepare a slurry; (3) coating the slurry of step (2) on the surface of the substrate, drying and sintering to obtain the glass-based composite fluorescent ceramic.

6. The preparation method according to claim 5, characterized in that: In step (1), the melting temperature is above 800°C. Preferably, in step (1), the melting time is 30 min-120 min.

7. The preparation method according to claim 5, characterized in that: In step (1), after melting, a heat preservation treatment is also performed, wherein the heat preservation treatment refers to heat preservation at the melting temperature, and the heat preservation time is 10min-60min. Preferably, in step (1), the rapid cooling treatment comprises rapidly cooling the molten glass at 0 to 100° C., and optionally crushing or grinding the molten glass.

8. The preparation method according to claim 5, characterized in that: In step (2), the organic solvent is selected from alcohols and cellulose. Preferably, in step (2), the mass ratio of oleyl alcohol to cellulose is 1-30:

1. Preferably, in step (2), the phosphor accounts for 0.1 wt% to 80 wt% of the total mass of the glass powder and the phosphor.

9. The preparation method according to claim 5, characterized in that: In step (3), the drying is performed at a temperature below 100°C. Preferably, in step (3), the sintering conditions include: a sintering temperature of 400° C.-600° C., and a holding time of 10-30 min.

10. Use of the glass-based fluorescent ceramic material according to any one of claims 1 to 4 in high-power LEDs.

Citation Information

Patent Citations

  • Preparation method for preparing large-size ultrathin fluorescent ceramic wafer through one-step molding

    CN112047758A

  • Garnet type fluorescent glass ceramic and preparation method thereof

    CN114920463A

  • Sapphire-based fluorescent glass ceramic and preparation method thereof

    CN115180835A

  • Fluorescent glass ceramic, preparation method thereof and LED lamp

    CN115893858A

  • Glass fluorescent ceramic, preparation method thereof and wavelength conversion device

    CN115893987A